2013
DOI: 10.7324/japs.2013.30125
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cypermethrin-treated lettuce (Lactuca sativa) on wistar rat liver

Abstract: In this study, assessment of the potential effect of cypermethrin-treated lettuce on the rat liver physiology is carried out. Cypermethrin-treated lettuce and three doses of cypermethrin (CY) were administered during 28 days to rats. Along the experimental period, animal behavior was assessed, and at the end of administration, some hepatic enzymes were studied. The decrease in rat body weight was noted and animals have soft feces. Results showed plasmatic concentrations of ALAT, ASAT and total bilirubin increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
1
11
0
1
Order By: Relevance
“…Several studies have reported the alteration of the levels of different biochemical parameters related to liver, kidney, and oxidative status functions in rats following exposure to CP. High elevation of aminotransferases (ALT and AST), ALP, creatinine, and MDA activities and decline of ChE, SOD, and CAT activities than the normal levels were reported by several investigators [16,17,50,51]. The results of those investigators support our findings regarding the effect of CP on the studied biochemical markers.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have reported the alteration of the levels of different biochemical parameters related to liver, kidney, and oxidative status functions in rats following exposure to CP. High elevation of aminotransferases (ALT and AST), ALP, creatinine, and MDA activities and decline of ChE, SOD, and CAT activities than the normal levels were reported by several investigators [16,17,50,51]. The results of those investigators support our findings regarding the effect of CP on the studied biochemical markers.…”
Section: Discussionsupporting
confidence: 92%
“…Aplikasi Sipermetrin menyebabkan akumulasi residu pada sayur dan buah hasil pertanian, apabila residu Sipermetrin dosis 10 mg/kg masuk ke dalam tubuh tikus wistar selama 28 hari akan berefek toksik sehingga dapat mempengaruhi sistem reproduksi (Adjrah et al, 2013). Kadar residu Sipermetrin dalam produk jambal roti ikan manyung yang diproduksi di Kabupaten Lamongan, Jawa Timur terdeteksi sebesar 0,027 -2,124 mg/kg (Amir, 2014), sedangkan pada kubis di Padang mencapai 2,08 mg/kg (Loekman dkk., 2005).…”
Section: Pendahuluanunclassified
“…Insecticides, the most widespread category of pesticides, are agents used globally in various industrial, agriculture, household, and veterinary practices (Hamid et al, 2012). Insecticides are potent and toxic environmental pollutants that exert public health problems through crop, soil, and water contamination (Adjrah et al, 2013). Neonicotinoids are a commercially recent class of insecticides that are extensively used instead of organophosphates, organochlorines, and carbamates insecticides, which are more harmful for mammals (Simon-Delso et al, 2015).…”
Section: Introductionmentioning
confidence: 99%